Unity and Diversity: Frames of Catholicity Among Catholic Campus Ministers - Day, Maureen K. (Review of religious research, 2021)
Scholars have explained many of the differences within the American Catholic population in terms of political division or polarization. Although Catholics are becoming increasingly politically bifurcated, to focus only on the political misses the specifically religious differences that also distinguish Catholics from one another. There have been substantial changes in the staffing of Catholic campus ministry in the last 20 years. To better understand these shifts and their implications for ministry, the Catholic bishops commissioned a survey of Catholic campus ministers in the United States. The survey answered some questions but raised others. A qualitative study that more deeply explored these questions was recommended. Using three “windows”—vocation, prayer and spirituality, and mission—this article explores the overlap and differences in frames of Catholicity among two types of Catholic campus ministers. Forty-five campus ministers from three geographic regions of the country were interviewed. Ten of these forty-five interviewees are “missionaries,” meaning they are recent college graduates who have obtained a several-week training from their missionary organization and are contracted to serve as a campus missionary for two years. Thirty-one of these are “professional ministers,” meaning they have a graduate degree in ministry and intend to have a long-term career in this field. Missionaries’ understandings of vocation, prayer and spirituality, and mission reveal that missionary-formed campus ministers operate out of a frame that emphasizes an individualist Catholicism. The professional ministers employ a frame that amplifies the communal aspects of Catholicism. These findings contribute theoretically to ideas in the framing literature, specifically in the fields of politics, emotions and identity. The way these frames might have an impact on ministry offerings and student formation are also discussed.